Peningkatan Kemampuan Menyimpulkan Isi Cerita rakyat melalui Model Pembelajaran Batangbesi - Agustiani, Iis; M, Mainilawati; H, Hetilaniar (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Regarding the problem of learning models, research researchers need to carry out class action research (PTK), so that learning outcomes can be improved, as expressed by Kasboillah (2008:13), that class action research (PTK) is important is one of the teacher's efforts to practice in various forms of activities which is carried out to increase the improvement of learning through approaches carried out directly by researchers. In this way, through this class action research activity the aim is to measure students' interests and abilities and find appropriate solutions to overcome the problems and difficulties faced by students in learning Indonesian, especially in mathematics. Summarize the contents of people's stories. This research uses the Class Action methodology. Peìneìliti by carrying out learning actions in class. Based on the results of the observations, the researchers concluded that the average answer was "yes" which indicated that the researchers implemented the items observed were 16 activity elements. In addition to providing a "yes" or "no" answer, observers are invited to provide comments, notes, or other information related to the implementation of the research conducted by the researcher. The observation results show that there are still several weaknesses. The advantages of the learning carried out in the first cycle are: the explanation of the material is less systematic, provides less motivation to students, and the suggestions given by observers are used as guidelines for implementing the lesson uklus II. Of the 17 elements observed, observations answered "yes" on average for 15 items, meaning that researchers had implemented all the items prepared. Despite this, observers still provide notes, namely that the provision of motivation needs to be increased so that understanding of the material can be optimally accepted by students.